The emerging politics of Antarctica - Brady, Anne-Marie, 1966- (Routledge advances in international relations and global politics ;, 2013)
"This book examines the post-Cold War challenges facing Antarctic governance. It seeks to understand the interests of new players in Antarctic affairs such as China, India, Korea and Malaysia, and how other key players such as Russia and the USA or claimant states such as New Zealand or France are coping in the new global order"--